THE INFLUENCE OF MELANIN ON THE PRODUCTIVITY OF STORE PIGS AT WEANING - Заїка, О. А. (Scientific Progress & Innovations, 2017)
The data on studying the effectiveness of adding melanin produced from yeast-like fungi Nadsoniella nigra strain Х-1 to the feed ration of piglets are presented. The positive effect of the given supplement on raising the average daily weight gains of store pigs has been found. In the experimental groups of animals to the feeds of which melanin with produced yeast-like fungi Nadsoniella nigra strain X-1 was added, the average daily weight gains of piglets during the period of weaning, and namely, at 45 days of age were 13,7 % higher comparatively to the index of the control group. Weighing of store pigs at 50 days of age, during the period of adaptation after weaning, has shown that the average daily weight gains in the experimental group of animals have raised and constituted 445 grams, which is 25 % higher compared to the indices of the control group. This is connected with the fact that melanin is a strong adaptogen.